Solar Fuel Production from Hydrogen Sulfide: An Upstream Energy Perspective - Mariia Ferree; Jan Kosco; Frédéric Laquai; Adrian Cavazos Sepulveda; Damian P. San Roman Alerigi (Advanced Energy & Sustainability Research, 2023)
Hydrogen sulfide is readily available in vast quantities in the subsurface as a byproduct of industrial processes. Hydrogen evolution from H2S can transform this highly toxic gas into a source of green fuel. Compared to water splitting, H2S dissociation is thermodynamically more favorable. However, feasible industrial‐scale catalytic technologies are not developed yet. The recovery of valuable chemicals using carbon‐neutral photocatalytic processes can capitalize on abundant solar irradiation and advanced semiconductors. The challenge is developing photocatalysts that can efficiently operate over the long term in the harsh environment of subsurface and industry, while utilizing as much of the light source spectrum as possible and providing optimum adsorption/desorption abilities of hydrogen and sulfur‐containing intermediates. Meeting these requirements demands improved kinematic models of photocatalytic H2S decomposition to assess the effect of high temperatures, pressures, mixtures of hydrocarbons, produced water, and other contaminants. Metal sulfides‐based catalysts may be the key to H2S decomposition in the subsurface (e.g., oil and gas reservoirs) and wellbores, but first they need to be upscaled as bulk, robust, and recyclable materials. This review presents a guide for the development of the upstream energy production technology via photocatalytic H2S conversion.